2009
DOI: 10.1111/j.1532-7795.2009.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Ethnic Identity Exploration and Ethnic Identity Affirmation and Belonging for Intergroup Attitudes Among Adolescents

Abstract: The present paper develops and tests two temporal models of the relationships among adolescents' ethnic identity exploration, ethnic identity affirmation and belonging, and attitudes toward their racial/ethnic ingroup and outgroups. Structural equation models for Euro-Americans, Asian Americans, and Latinos revealed that all hypothesized relationships were positive and significant. The model in which ethnic identity exploration (at Time 1) predicts ethnic identity affirmation and belonging (at Time 2) was supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 13 publications
(19 reference statements)
7
24
0
Order By: Relevance
“…No support was found for this model in either the ethnic minority or gay/lesbian samples. A recent study by Whitehead, Ainsworth, Wittig and Gadino (2009) further corroborates the direction of our predictions. Using a longitudinal design, Whitehead et al assessed the association between identity achievement and affirmation in an intergroup context where Euro-American, Asian American and Latino adolescents reported on their feelings towards their own ethnic group as well as those toward other ethnic groups.…”
Section: Discussionsupporting
confidence: 90%
“…No support was found for this model in either the ethnic minority or gay/lesbian samples. A recent study by Whitehead, Ainsworth, Wittig and Gadino (2009) further corroborates the direction of our predictions. Using a longitudinal design, Whitehead et al assessed the association between identity achievement and affirmation in an intergroup context where Euro-American, Asian American and Latino adolescents reported on their feelings towards their own ethnic group as well as those toward other ethnic groups.…”
Section: Discussionsupporting
confidence: 90%
“…A status approach focuses on the extent to which individuals have explored the implications of their ethnicity and feel a sense of pride at being a member of a particular group (e.g., Phinney, 1992). Status research has suggested that ethnic identity emerges during adolescence and early adulthood, with ethnic identity exploration preceding the development of pride (Phinney, 2008;Syed & Azmitia, 2009;Whitehead, Ainsworth, Wittig, & Gadino, 2009). Longitudinal data have shown increases in exploration from early to middle adolescence, with few systematic changes during the high school years (French, Seidman, Allen, & Aber, 2006;.…”
mentioning
confidence: 96%
“…More systematic and progressive changes appear among emerging adults during the transition to college and over the college years (Phinney, 2008;Syed, Azmitia, & Phinney, 2007). A strong ethnic identity-one based on exploration of one's traditions and culture and characterized by pride-is a positive force for individual well-being and for attitudes towards other groups (Phinney, 1992;Whitehead et al, 2009), with higher levels of exploration and pride being associated with multiple positive outcomes (Eccles, Wong, & Peck, 2006;Phinney, 1992;Syed & Azmitia, 2008Syed et al, 2007). Thus, understanding how individuals explore their identities and develop a sense of pride in their ethnic group is important.…”
mentioning
confidence: 98%
“…Autonomy is fostered by exercising few rules or regulations in daily life, hence much freedom is granted to explore the environment independently in order to learn how to self-manage well ("iesbirgejupmi") (Bongo, 2012). Such parental practices may represent a cultural competence that help sustain ethnic identity and even pride (Javo et al, 2003;Whitehead, Ainsworth, Wittig, & Gadino, 2009). A strong ethnic identity is generally found to buffer against harmful effects of discrimination (Yip, Gee, & Takeuchi, 2008).…”
Section: Mean Score Differences In Mental Health and Wellbeing Betweementioning
confidence: 99%